Interface and strain effects on the H-sorption thermodynamics of size-selected Mg nanodots. (22nd June 2016) - Molinari, Alan; D'Amico, Federico; Calizzi, Marco; Zheng, Yan; Boelsma, Christiaan; Mooij, Lennard; Lei, Yong; Hahn, Horst; Dam, Bernard; Pasquini, Luca
Abstract: This work deals with the thermodynamics of hydride formation in 3-D nanoconfined Mg. Two ensembles of nearly monodisperse Mg nanodots (NDs) with different diameters (60 and 320 nm), were grown by the template nanopatterning method, using ultra-thin alumina membranes (UTAMs) with ordered porosity as evaporation masks. Multilayer NDs consisting of 30 nm Mg, 5 nm Ti and 5 nm Pd were deposited on UTAM-coated glass substrates by molecular beam epitaxy. The lateral surface of the NDs is constituted by native MgO. The morphology of the NDs was characterized by field emission scanning electron microscopy and atomic force microscopy. Hydride formation and decomposition was studied at low temperature (363–393 K) by means of optical hydrogenography. Compared to bulk Mg, the plateau pressure for hydrogen absorption in NDs exhibits an upward shift, which is larger for small NDs. Differently, the desorption plateau pressure is almost the same for the two NDs size and is lower than for bulk Mg. These hydrogen sorption features are discussed in the frame of a model that takes into account both interface energy and elastic strain energy in the constrained nanodots. The onset of plastic deformation, marked by a high pressure hysteresis between hydrogen absorption and desorption isotherms, limits the extent of hydride destabilization that can be achieved by elastic strain engineering. Graphical abstract: Highlights: Size-selected Magnesium nanodots were synthesized by template nanopatterning method. Thermodynamics oh hydrogen sorption was measured at low temperature (90–120 °C). Size-dependent hydrogen absorption pressure and hysteresis appears in Mg nanodots. Results are explained by a model based on interface and elastic strain energy.